Bridging the Gap(s) between ‘European’, ‘Balkan’ and ‘Greek’ Archaeolog(ies)y - Giamakis, Christos (Ex Novo: Journal of Archaeology, 2024)
The present paper examines the relationship between the terms ‘European’ and ‘Balkan’ archaeology and the way this is reflected on archaeology in Greece. More specifically, it discusses three main factors, most notably the seemingly sequential progress of archaeology, access to funding, and university rankings and publishing schemes all of which contribute to the perceived ‘backwardness’ of ‘Balkan’ archaeolog(ies)y when compared to ‘European’ ones. The chasm between these two, and the way this influences archaeological practice in Greece is then studied by comparing archaeology in Northern Greece, an area traditionally perceived as the link between the wider Balkans and Southern Greece, a region regarded as the cornerstone of the ‘Western’ world. The role of the foreign archaeological institutions and the Greek state in this divide is studied, arguing that the approaches of both towards Northern Greece are hindering the region from reaching its full archaeological potential. The paper concludes by providing some preliminary thoughts on future steps moving beyond dualisms and towards a more inclusive archaeology.